Numerical study of DC-biased AC-electrokinetic flow over symmetrical electrodes - Ng, Wee Yang (2013)
This paper presents a numerical study of DC-biased AC-electrokinetic (DC-biased ACEK) flow over a pair of symmetrical electrodes. The flow mechanism is based on a transverse conductivity gradient created through incipient Faradaic reactions occurring at the electrodes when a DC-bias is applied. The DC biased AC electric field acting on this gradient generates a fluid flow in the form of vortexes. To understand more in depth the DC-biased ACEK flow mechanism, a phenomenological model is developed to study the effects of voltage, conductivity ratio, channel width, depth, and aspect ratio on the induced flow characteristics. It was found that flow velocity on the order of mm/s can be produced at higher voltage and conductivity ratio. Such rapid flow velocity is one of the highest reported in microsystems technology using electrokinetics.